PUTUSAN MAHKAMAH KONSTITUSI YANG TIDAK DILAKSANAKAN DALAM PENGUJIAN UNDANG-UNDANG DITINJAU DARI ASAS ERGA OMNES: (Analisis Putusan Mahkamah Konstitusi Nomor 1/PUU-XI/2013) - Fadly Ikhsan Pradana; Wicipto Setiadi (Indonesian State Law Review, 2021)
The Indonesian Constitutional Court was formed based on the Amendment to the 1945 Constitution of the Republic of Indonesia.. The Constitutional Court in giving decisions must be implemented and obeyed in general (erge omnes). However, there are still state officials who do not implement the Constitutional Court decisions. Based on the 2019 academic report issued by the Faculty of Law, Trisakti University, 22 percent did not carry out the decisions ordered by the Constitutional Court. The research method used by the author is normative juridical using library materials. There is a Constitutional Court Ruling that cannot be implemented, namely the imposition of Article 335 of the Criminal Code with an unpleasant phrase. Based on this, the provision has no binding law. The factor of the inability to implement the Constitutional Court decision is that there is no executing institution and support from political parties. It can be summarized that there is a need for an executor and given a clear time statement.